Peran Media Youtube dalam Pembelajaran Daring pada Materi Keterampilan Berbicara Bahasa Arab - Prasista, Nita; Garancang, Sabaruddin; Munawwir, Ahmad; Lukita, Rani (Al asma : Journal of Islamic Education, 2023)
This research is entitled The Role of Youtube Media in the Online Period in Arabic Speaking Learning for Class VII.1 Students of MTsN 2 Bulukumba which aims to determine the role of YouTube media in helping Arabic learning activities online and find out the obstacles and solutions faced by teachers and students in class VII. 1 MTsN Bulukumba. This research includes qualitative research with qualitative descriptive methods. This research approach is a scientific study approach used in discussing research objects according to academic relevance and the author's department/study program which is correlated with the use of technological media as a learning support. The data in this study were obtained through observation techniques, interview techniques, and documentation. Based on the results of the research, YouTube is the right solution for learning Arabic during distance learning during a pandemic in class VII.1 MTsN 2 Bulukumba because it explains that learning via YouTube can be accessed anytime and anywhere, learning materials are assisted with media that displays pictures/ animation and sound so as not to bore students. The implications of this research in terms of scientific utilization are expected to be able to contribute to the development of science, especially in learning Arabic language education and getting to know technology.